1998
DOI: 10.1182/blood.v91.4.1280
|View full text |Cite
|
Sign up to set email alerts
|

No Neuronal Regulation of Murine Bone Marrow Function

Abstract: Bone marrow is innervated by efferent (sympathetic) and afferent nerves, but it is not clear whether these nerves affect cell formation or release in any significant way. To elucidate this problem, we studied mice neonatally sympathectomized with 6-hydroxydopamine and adult mice in which one hind limb was surgically denervated. Progenitor and transit cell numbers and proliferative activity were estimated in bone marrow, blood, and spleen. In addition, we performed unilateral electrical stimulation of nerve fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The presence of cognate receptors for neuronal transmitters on bone marrow cells supports this notion (Maestroni & Conti, 1994;Rameshwar & Gascon, 1995;. Surprisingly therefore, we could not demonstrate any function of innervation on mouse tibial bone marrow function, by denervation, electrical nerve stimulation or neonatal chemical sympathectomy (Benestad et al, 1998a). However, these findings have been challenged on methodological grounds (Maestroni, 1998;Miyan et al, 1998a).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…The presence of cognate receptors for neuronal transmitters on bone marrow cells supports this notion (Maestroni & Conti, 1994;Rameshwar & Gascon, 1995;. Surprisingly therefore, we could not demonstrate any function of innervation on mouse tibial bone marrow function, by denervation, electrical nerve stimulation or neonatal chemical sympathectomy (Benestad et al, 1998a). However, these findings have been challenged on methodological grounds (Maestroni, 1998;Miyan et al, 1998a).…”
supporting
confidence: 72%
“…The irides were mounted on coated glass slides. Smears were made from marrow plugs (Benestad et al, 1998a). These preparations were immediately processed for glyoxylic acid-induced fluorescence or immunohistochemistry with antibodies.…”
Section: Animalsmentioning
confidence: 99%
“…Chemical denervation of the sympathetic nervous system with 6-hydroxydopamine did not a¡ect marrow blood £ow either (Iversen et al 1994a). Moreover, sympathetic denervation did not change either marrow metabolism (Iversen & Skrede 1994) or cellular di¡erentiation and subsequent marrow release of leucocytes (Benestad et al 1991). In contrast, stimulation of isolated carotid sinus baroreceptors augmented marrow blood £ow in the anaesthetized dog, while activation of sympathetic pathways by baroreceptor dea¡erentation in anaesthetized cats decreased marrow blood £ow (Gross et al 1979).…”
Section: Neuronal Vasomotoractivitymentioning
confidence: 86%
“…This indicates that the mobilization of neutrophils from the bone marrow might be dependent on specific macrophage signaling, or the concentration of humoral factors must exceed a threshold to achieve mobilization. The mobilizing signal to the bone marrow is probably of humoral origin, since we previously found that production and release of neutrophils from the bone marrow during the development of a sterile peritonitis in mice did not depend on the innervation of the marrow (24). Surprisingly, the mobilization of neutrophils to the blood was apparently not affected early in the inflammatory process, since the 5 hours neutrophil blood concentration was not significantly different in macrophage‐depleted and control rats.…”
Section: Mobilization Of Bone Marrow Neutrophils During Sterile Peritmentioning
confidence: 99%